Challenges and Opportunities for Islamic Religious Education Teacher Professionalism in the Utilization of Technology - Munawir; Afina Aulia Fahri; Nisak, Laila Syafira (Jurnal Hadratul Madaniyah, 2025)
Teacher professionalism in the context of Islamic Religious Education (PAI) concerns various competencies, namely pedagogical, personal, social and professional skills that an educator must have. A PAI teacher is not only tasked with delivering material, but also plays an important role in instilling Islamic values ​​in the learning process. In the digital era, the challenges faced by PAI teachers are increasingly complex, including moral crises, demands for digital literacy, curriculum changes, and the need to improve the quality of human resources. However, technological advances also provide great opportunities for PAI teachers to improve their professionalism. By utilizing interactive learning, more flexible access to materials, and developing digital skills, they can create more engaging and effective learning experiences for students. Therefore, the professional development of PAI teachers through technology-based training and development needs to continue to be supported so that they are ready to face the challenges of globalization and meet educational needs in the modern era.